Non-Fungible Tokens (NFTs) Phenomenon : Understanding, Trends, and Implications in Era 5.0 - Isnaini, Teuku; Boihaki, Boihaki (Fakultas Ekonomi Universitas Jabal Ghafur, Sigli. Aceh, 2024)
This research presents an in-depth review of the Non- Fungible Tokens (NFTs) phenomenon in the context of Era 5.0. With a focus on understanding, trends, and implications, this research introduces the basic concepts of NFTs as well as the history of their development in decentralized digital ecosystems. Through a comprehensive qualitative approach, this research analyzes related literature, reveals current trends in the use of NFTs, and highlights their economic, cultural, and social implications. This research methodology includes literature studies, market data analysis, and interviews with industry experts. The research results show that NFTs are making a significant impact in the digital economy, opening up new opportunities for digital content monetization, and uniquely recognizing ownership rights. Although adoption of NFTs is increasing, we also identified challenges such as inequality of access and environmental impacts that need to be addressed. It is hoped that the results of this research will provide valuable insight for academics, practitioners and policy makers in understanding the role and potential of NFTs in the context of continuing technological and economic developments.